PENGARUH PENGUNGKAPAN LINGKUNGAN BERBASIS GRI DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN PERUSAHAAN PERTAMBANGAN DI BEI - Ardelia Nopianti; Meliana Puspitasari; Awaliawati Rachpriliani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study analyzed 195 mining issuers' data from the Indonesia Stock Exchange (IDX) for the 2020–2024 period using multiple linear regression to examine the effect of environmental disclosure (GRI index) and company size (ln total assets) on ROA, ROE, and NPM. Partial test results indicate that environmental disclosure has no effect, while company size has a significant negative effect. Simultaneous test results confirm that both variables jointly influence financial performance. This finding suggests that the benefits of environmental disclosure are not readily apparent, while large-scale companies tend to experience decreased profitability due to high operational costs in the short term.